(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Although COVID-19 has impacted many children, severe disease is rare and most recover with supportive care. Manifestations are diverse and often nonrespiratory. Adolescents/children with medical comorbidities are at risk for severe respiratory compromise. The most serious manifestation in previously healthy children is a delayed multisystem inflammatory syndrome with cardiac compromise in severe cases. Anti–SARS-CoV-2 monoclonal antibodies are available for adolescents at risk of progression and not hospitalized. Therapeutic options for severe respiratory disease with hypoxia include remdesivir and glucocorticoids. Therapies for multisystem inflammatory syndrome in children include intravenous immunoglobulin and glucocorticoids. Refractory cases may benefit from additional immunomodulators.